2017
DOI: 10.1002/art.40547
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Receptor 1 Antagonist SAR100842 for Patients With Diffuse Cutaneous Systemic Sclerosis

Abstract: SAR100842, a selective orally available LPA receptor antagonist, was well tolerated in patients with dcSSc. The MRSS improved during the study although the difference was not significant, and additional gene signature analysis suggested target engagement. These results need to be confirmed in a larger controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 24 publications
1
42
0
1
Order By: Relevance
“…Although there is no existing approach to targeting ATX-LPA axis for cancer treatment, there is now sufficient evidence to establish that LPA is a significant inducer that increases tumor growth, metastasis, and loss of efficacy of chemotherapy and RT. Blocking LPA formation and signaling as part of cancer treatment has become possible because at least three inhibitors against LPA signaling have proven to be safe in clinical trials [ 144 , 145 , 158 ]. GLPG1690, which is an ATX inhibitor, is currently in a Phase 3 trial for IPF [ 144 ].…”
Section: Future Perspectivementioning
confidence: 99%
“…Although there is no existing approach to targeting ATX-LPA axis for cancer treatment, there is now sufficient evidence to establish that LPA is a significant inducer that increases tumor growth, metastasis, and loss of efficacy of chemotherapy and RT. Blocking LPA formation and signaling as part of cancer treatment has become possible because at least three inhibitors against LPA signaling have proven to be safe in clinical trials [ 144 , 145 , 158 ]. GLPG1690, which is an ATX inhibitor, is currently in a Phase 3 trial for IPF [ 144 ].…”
Section: Future Perspectivementioning
confidence: 99%
“…In contrast to previous findings of direct TRP channel activation [545], LPA18:1 more substantially activates satellite glial cells and Schwann cells, suggesting an indirect neuromodulatory action [546]. LPA receptor antagonists are under development, and being tested for a number of pathologies, with analgesia not as the primary focus [539,547,548].…”
Section: Y D R O X Y E I C O S a T E T R A E N O I C A C I D S ( H E mentioning
confidence: 76%
“…Overall, our unprecedented results obtained with SAR100842 in animal models of skin fibrosis using therapeutics protocols and our data in dermal fibroblasts from systemic sclerosis patients indicate that the inhibition of LPA 1 receptor signalling could be a promising therapeutic strategy in both patients with inflammatory as well as non‐inflammatory subtypes of systemic sclerosis. Indeed, a recently performed Phase 2 trial with SAR100842 demonstrated the safety of the approach in these patients (Allanore et al, 2018; Khanna et al, 2015).…”
Section: Discussionmentioning
confidence: 99%